Introducing Basic English to Indonesian Heritage Children in Japan Through a Winter Camp Community Service Program - Salmah; Hesty Widiastuty; Nur Syamsiyah Sriman (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study analyzes a Winter Camp program introducing basic English to Indonesian heritage children in Japan, addressing pedagogical challenges for receptively bilingual learners dominant in Japanese. Method: Employing a descriptive qualitative approach, data were collected through observation, documentation, and reflective notes during alphabet instruction, games, and interactive competitions. Practical Applications: Findings demonstrate that immersive, joy-based, activity-driven strategies effectively enhance English exposure for heritage learners in multilingual diaspora contexts, offering replicable models for community-based language initiatives. Conclusion: The Winter Camp successfully fostered engagement and enthusiasm among linguistically diverse participants, providing practical insights for designing context-sensitive English instruction within community service programs abroad.